The Martian Crustal Magnetic Field - Mittelholz, Anna; Johnson, Catherine L. (Frontiers in Astronomy and Space Sciences, 2022)
Mars' crustal magnetic field holds information on the planet's interior evolution and exterior processes that have modified the crust. Crustal magnetization records an ancient dynamo field that indicates very different interior conditions in the past, possibly linked to the presence of a thicker early atmosphere. Current data sets have provided a wealth of information on the ancient magnetic field, and on the acquisition and modification of magnetization in the crust. However, many puzzles remain regarding the nature and origin of crustal magnetization, and the timing and characteristics of the past dynamo. Here we use recent advances in understanding martian magnetism to highlight open questions, and ways in which they can be addressed through laboratory analysis, modeling and new data sets. Many of the outstanding key issues require data sets that close the gap in spatial resolution between available global satellite and local surface magnetic field measurements. Future missions such as a helicopter, balloon or airplane can provide areal high resolution coverage of the magnetic field, vital to major advances in understanding planetary crustal magnetic fields.